Efek pemoderasi materialism pada pengaruh money ethics terhadap tax evasion - Silmi, Sarah Aghnia (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This research aims to analyze the effect of money ethics on tax evasion and the effect of materialism as a moderating variable. The research method needed in this research is quantitative. The location in this research is the Tax Service Office (KPP) Pratama Tegallega. The data collection technique in this research is primary data by distributing questionnaires to respondents. The population in this research is individual taxpayers. The sampling technique used was convenience sampling with 100 individuals obtained. The data analysis technique used is descriptive statistics using the SMARTPLS application. Testing the data using path diagrams, goodness of fit, outer model and inner model. The results of this research indicate that money ethics has an effect on tax evasion and materialism strengthens the relationship between money ethics and tax evasion, so the hypothesis presented by the researcher is acceptable.